Rancangan Pengukuran Kinerja Perusahaan Dengan Metode Balanced Scorecard Pada CV. Angkasa Raya Teluk Kuantan - Tasya Vivaldie; Mariaty Ibrahim (Komunitas Dosen Indonesia, 2024)
This study aims to assess performance using the balanced scorecard method across various perspectives: financial, customer, internal business processes, and growth and learning. The research employs a quantitative approach with primary and secondary data sources, involving 40 respondents from CV Angkasa Raya Teluk Kuantan employees, selected through accidental sampling. Data analysis, including validity and reliability tests, is conducted using SPSS 25. The findings indicate that (1) the financial perspective for CV Angkasa Raya Teluk Kuantan is generally positive, (2) the customer perspective reveals the company's ability to achieve customer satisfaction, (3) the internal business process perspective reflects favorable results in the areas of innovation, operations, and after-sales service, and (4) the growth and learning perspective suggests satisfactory employee satisfaction and effective training programs. The study provides a comprehensive assessment of performance measurement using the balanced scorecard method, offering insights into the company's strengths across various dimensions.